2014
DOI: 10.1152/ajpheart.00924.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone reduces angiotensin II-induced COX-2 expression through inhibition of ROS production and ET-1 transcription in vascular cells from spontaneously hypertensive rats

Abstract: Glitazones have anti-inflammatory properties by interfering with the transcription of proinflammatory genes, such as cyclooxygenase (COX)-2, and with ROS production, which are increased in hypertension. This study analyzed whether pioglitazone modulates COX-2 expression in hypertension by interfering with ROS and endothelin (ET)-1. In vivo, pioglitazone (2.5 mg·kg(-1)·day(-1), 28 days) reduced the greater levels of COX-2, pre-pro-ET-1, and NADPH oxidase (NOX) expression and activity as well as O2 (·-) producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Here, we observed the NAD(P)H oxidase activity in VSMC induced by exposure to AngII for 1h was reduced by the MyD88 inhibitor ST‐2825 (Figure A). We have also reported that AngII increases oxidative stress in VSMC through JNK1/2 MAPK and NF‐κB (Pérez‐Girón et al ., ). The phosphorylation of JNK1/2, induced by exposure to AngII for 10 min, was reduced by the TLR4 inhibitor CLI‐095 (Figure B).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Here, we observed the NAD(P)H oxidase activity in VSMC induced by exposure to AngII for 1h was reduced by the MyD88 inhibitor ST‐2825 (Figure A). We have also reported that AngII increases oxidative stress in VSMC through JNK1/2 MAPK and NF‐κB (Pérez‐Girón et al ., ). The phosphorylation of JNK1/2, induced by exposure to AngII for 10 min, was reduced by the TLR4 inhibitor CLI‐095 (Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…Another signalling pathway recruited by TLR4 activation, via the MyD88‐dependent pathway, is the MAPK cascade (Kawai and Akira, ). Previously, we have shown that JNK and NF‐κB contributed to the oxidative stress induced by AngII (Pérez‐Girón et al ., ). Here we showed, in VSMC, that AngII‐induced NAD(P)H oxidase activity was reduced by a specific MyD88 inhibitor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is noteworthy that the basal ERK phosphorylation in vascular cells is mediated in part by reactive oxygen species (ROS), including superoxide (O 2 − ) [57, 58]. In addition, PIO has been shown to inhibit NADPH oxidase-mediated generation of ROS in aortic tissues and VSMCs [59, 60]. Thus, it is likely that PIO inhibits the basal ERK activation by suppressing ROS production in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…NOX-1 is an inducible gene and its expression is increased in vascular cells by several pro-inflammatory stimuli including AngII, interferon-γ (IFN-γ) and platelet derived growth factor (PDGF) [811]. Various transcription factors such as ATF-1 [12,13] or STAT [9] have binding sites in NOX-1 promoter and play an important role in its inducible expression.…”
Section: Introductionmentioning
confidence: 99%